2004
DOI: 10.1590/s1806-83242004000300004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of yeasts in the oral cavity of children treated with inhaled corticosteroids

Abstract: The aim of this study was to observe the prevalence of Candida spp. in the oral cavity of children undergoing treatment with inhaled corticosteroids. Thirty children treated with inhaled corticosteroids and thirty control children were studied. Saliva samples were collected through oral rinses with phosphate buffered saline (PBS). The samples were plated on Sabouraud's dextrose agar and incubated at 37 degrees C for 48 h. After this period, the number of colony-forming units per ml (cfu/ml) of saliva was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…These results agree with previous studies reporting higher prevalence of non-albicans species in patients with different predisposing factors (13,2). Probably, the imbalance in the microbiota favored the adherence of other species of Candida, which normally would not be able to adhere.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with previous studies reporting higher prevalence of non-albicans species in patients with different predisposing factors (13,2). Probably, the imbalance in the microbiota favored the adherence of other species of Candida, which normally would not be able to adhere.…”
Section: Resultssupporting
confidence: 93%
“…The incidence of Candida spp. in the oral cavity and the reasons for the establishment of infections caused by these microorganisms have been associated to immunosuppression, endocrine disorders, mucosal lesions, poor oral hygiene, and long-term treatment with antibiotics or corticosteroids (3,13).…”
Section: Br Opportunistic Microorganisms In Tuberculosis Patientsmentioning
confidence: 99%
“…In the present study, a positivity of 30% was obtained for Candida in the control group and a wide range of Candida species was isolated from children who used inhaled corticosteroids, a condition that predisposes individuals to the development of oral candidiasis 15 . Martins et al 11 showed that the prevalence of yeast species isolated from the oral cavity of healthy children in the United States and Brazil was approximately 30% and 47%, respectively.…”
Section: Discussionmentioning
confidence: 48%
“…Komiyama et al 15 reported that the Candida yeasts isolated from the oral cavity of children represent 45% -65% of the total fungal isolates and that Candida albicans was the most frequent species in this region, as reported in other studies in the literature 4,[8][9][10]14 . In the present study, a positivity of 30% was obtained for Candida in the control group and a wide range of Candida species was isolated from children who used inhaled corticosteroids, a condition that predisposes individuals to the development of oral candidiasis 15 .…”
Section: Discussionmentioning
confidence: 65%
“…Lower values were reported by Barbieri 11 who found that 12 out of 38 children (31.57%) hosted yeasts of the genus Candida, and Komiyama et al 25 observed the presence of Candida spp. in the oral microbiota of 30% of the healthy children he evaluated.…”
Section: Presence Of the Genus Candida In Childrenmentioning
confidence: 72%